Gross And Histopathological Studies On Kidneys Of Japanese Quail (Coturnixcoturnix Japonica) - Singh , N.K.; Gautam , A.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Investigation was undertaken to study the incidence and nature of disorders in kidney of different age groups of Japanese quail. Out of three hundred two birds, 127 quails showed alterations in their kidneys, 25 had changes of hyperaemia prominent in cortex than medullary region with one or more cysts. Thirty one quails had shown changes of haemorrhages whereas 48 showed changes of nephritis and 20 had the changes of acute interstitial nephritis. Remaining birds were found normal except mild swelling.
Keywords: Gross; Histopathology; Kidney; Japanese quail